OPTIMIZATION OF ENZYMATIC HYDROLYSIS CONDITIONS OF SEAWEED (Gracilaria fisheri) PROTEIN BY USING ALCALASE® TO OBTAIN MAXIMUM ANGIOTENSIN-I-CONVERTING ENZYME (ACE) INHIBITORY ACTIVITY - AMIN, AMIZA MAT; LEE , WONG SHER; SHARMIN, KAZI NAZIRA (Malaysian Applied Biology, 2020)
This study aimed to optimize the enzymatic hydrolysis conditions of Gracilaria fisheri protein by using Alcalase® to obtain maximum angiotensin-I-converting enzyme (ACE) inhibitory activity. Firstly, the seaweed protein was extracted using cellulase, sonication, and ammonium sulphate treatment, before dialysis and lyophilization. The yield of lyophilized seaweed protein extract was 8.75% with a protein content of 66.4%. An optimization study for protein hydrolysis condition was performed by employing a three-level face-centered central composite design (CCD) using Design-Expert software. Four parameters used were pH (6.5 – 8.5), temperature (50 – 60°C), hydrolysis time (60 – 180 min), and Alcalase® to substrate ratio (E/S) (1.25 – 2.50%). Thirty runs of protein hydrolysis conditions with 6 center points were employed. The supernatant of the resulting protein hydrolysates was then lyophilized and analyzed for ACE inhibitory activity. This study found that the quadratic model could be used to explain the relationship between hydrolysis conditions of G. fisheri protein and ACE inhibitory activity. The optimum condition to obtain maximum ACE inhibitory activity was at pH of 7.5, the temperature of 54.6°C, hydrolysis time of 175 min, and E/S of 1.47%. The half-maximal inhibitory concentration (IC50) of the seaweed protein hydrolysate at optimum condition was 2.97 ± 0.37 mg/mL.